ANALYSIS ON FLOW PRESSURE IN THE PNEUMATIC BRAKING SYSTEM OF FHS-RDE USING FLUENT 6.3 SOFTWARE - Sukmanto Dibyo; Ign. Djoko Irianto; V. I. Sri Wardani; Marliyadi Pancoko (Pusat Teknologi Dan Keselamatan Reaktor Nuklir (PTKRN), 2020)
The High Temperature Gas Cooled Reactor (HTGR) is considered as one of the nuclear reactors of generation-IV type in the future. The fuel handling system is one of the important processes in HTGR as well as in the design of Reaktor Daya Eksperimental (RDE). In the Fuel Handling System (FHS), the fuel pebble is transferred pneumatically along the pipe using carrier gas into the core of the reactor. Therefore, the pneumatic is an important system in operation stability of FHS. During the developing process of FHS-RDE, a branch pipe as a braking pipe system is provided on top of the pneumatic system to reduce the speed of the fuel discharged from the pneumatic pipe. The pneumatic pipe has an inner diameter of 65 mm and 20 m in length, whereas a branch pipe diameter for the braking system is 30 mm. The pneumatic system pressure is greater than the reactor cooling system pressure of 3.0 MPa. This work was performed to investigate the pressure drop and flow pattern of the braking system of FHS by various carrier gas inlet pressure. The analysis was carried out by Fluent 6.3 Software. Based on the design parameter of FHS used in the analysis, the results show that the performance of the braking system is not significant to reduce the pressure in the top region of the pneumatic pipe. To obtaining a significant reduction in pressure, and evaluation on the design of the branch pipe as well as the radius of curvature of the bend at the top pipe is suggested.Keywords: Pneumatic pipe, pressure, braking system, fuel handling of RDE, carrier gas